PENERAPAN STANDAR PROSEDUR OPERASIONAL DENGAN SISTEM APLIKASIPENERBITAN POLIS ASURANSI JIWA SYARIAH KUMPULAN PT XYZ - LUkman Anthoni (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2017)
ABSTRACT Standard Operating Procedures (SOPs) of the Company on the work process the publishing group life insurance policies differ from one another. In essence, the service is done to maximize the Company's resources in place to provide maximum service to the policyholder. The process of publishing sharia group life insurance policy in this case includes the process at some Division or Section Unit of the Company. To be able to give good results and the determination of the application process flow of work must be agreed in advance by the Division or Section Unit linked by also considering processing time at the Division or Section Unit.To run the policy issuance process, then there is a relationship application of working procedures with the application system used in the issuance of life insurance policies. The application system used must be in accordance with the procedures for issuing the policy. In practice, the Company adjusted the integrated application system to follow the procedures for issuance of policy set by the company. This is certainly to reduce errors, say human error and improve the effectiveness and efficiency of the Company's operations.In determining the working procedures associated with other Unit Parts suggested Companies can pay attention to every working procedures in each section related unit, as this will be tied to the Company's accumulated time required to issue a group life insurance policy.